2019
DOI: 10.3390/buildings9050135
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Design: Sustainability in the Decision-Making Process

Abstract: This article discusses the potential of introducing sustainability in the architectural design method so that building solutions can contribute to sustainable development. Sustainability has introduced a new pattern to the architecture practice, which involves important modifications in the teaching of architecture in what regards to the design methods to students but also practitioners, in order to provide more comfort for present and future generations. In the design phases of the architectural design, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The concept of sustainable development has been radically developed since the Earth Summit held in 1992 by the United Nations. According to Massod's recent research in 2017, the green architecture has been suggested as a mega trend that normally focuses on the relationship between architecture and nature, enabling energy to be used in new ways, such as solar and wind renewals, to meet both basic requirements of the ecological architecture and user needs [18].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of sustainable development has been radically developed since the Earth Summit held in 1992 by the United Nations. According to Massod's recent research in 2017, the green architecture has been suggested as a mega trend that normally focuses on the relationship between architecture and nature, enabling energy to be used in new ways, such as solar and wind renewals, to meet both basic requirements of the ecological architecture and user needs [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the specific dynamics of each IDP team depends on the planning and design model followed and on the decision-making process adopted. In some projects, simpler, more flexible and more inclusive processes are used which could provide stronger connections with the objectives of sustainable development [48,58,62]. Thus, even in an IDP context, the main pillars of building design can still be considered architectural, engineering, or operational in nature.…”
Section: The Integration Of Sustainability In Designmentioning
confidence: 99%
“…One of the assumptions used in the study is the disconnect of the current planning and design process from the sustainable development objectives. Although the current prevailing practices do consider certain environmental, social and economic factors in the design, the researchers were unable to find theoretical or practical models which have sustainable development, in its broad definition, as their core objective (as opposed to cost, energy, or sustainability credits optimization objectives)-this assumption is supported by the work of [43,51,[58][59][60][61][62][63][64]. Additionally, this research does not explicitly compare, analyze or map the interaction between these rating and certification tools and the SDGs-thus not highlighting the possible synergies between the 2030 Agenda and the green building rating tools.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations